Poligami dan Kesetaraan Gender: Perspektif Pancasila dan Kajian Islam serta Implikasi Konstitusi: Polygamy and Gender Equality: Pancasila Perspectives and Islamic Studies and Constitutional Implications - Ahmad Muhammad Mustain Nasoha; Insannia Azzura Amananta; Melati Fajar Setiowati; Sabrina istigfara, Airin (DIRASAH: Jurnal Kajian Islam, 2025)
This research aims to understand the relationship between the practice of polygamy and gender equality from the perspective of Pancasila, the constitution and Islamic teachings. This research uses a qualitative method with a case study approach. The research results show that the practice of polygamy, from the perspective of Pancasila, the Indonesian constitution and Islamic teachings, faces challenges in achieving the principles of justice and gender equality guaranteed by the state. Islam permits polygamy with strict conditions to ensure justice, but implementing this principle in practice often experiences difficulties and has significant social impacts. Therefore, more gender-sensitive legal reform is needed to protect women's rights and achieve gender equality in accordance with the principles of Pancasila and the values ​​of justice in Islam.